Development and application of WHONET software in hospital antibiogram - Manoj Dikkatwar; Jitendra Vaghasiya (Elsevier, 2023)
Antibiotic resistance is an emerging issue that requires a track on antimicrobial resistance pattern in an institution to prescribe appropriate empirical therapy. Antibiogram that's an aggregate of antimicrobial susceptibility profile within an institution provides a better understanding of empirical and prophylactic use of antimicrobials. It also focuses on M39 guidelines published by Clinical and Laboratory Standard Institute for developing accurate and reliable data of antibiograms. The data for this review has been extracted from literature databases such as Medline/PubMed, Scopus, Web of Science, Embase and the Cochrane Library. This literature highlights the importance of clinical pharmacists in developing antibiogram by preventing antimicrobial resistance, types of antibiogram, history and development, need, role of hospital and microbiological laboratory and Clinical and Laboratory Standard Institute guidelines. Additionally, the significance of WHONET software for developing and analysis of results rather than using old/traditional methods, limitations, and future considerations of antibiogram has also been described.